Duhem's problem revisited: logical versus epistemic formulations and solutions. - Dietrich, Michael; Honenberger, Phillip (Synthese, 2020)
When the results of an experiment appears to disconfirm a hypothesis, how does one know whether it's the hypothesis, or rather some auxiliary hypothesis or assumption, that is at fault? Philosophers' answers to this question, now known as "Duhem's problem," have differed widely. Despite these differences, we affirm Duhem's original position that the logical structure of this problem alone does not allow a solution. A survey of philosophical approaches to Duhem's problem indicates that what allows any philosopher, or scientists for that matter, to solve this problem is the addition of epistemic information that guides their assignment of praise and blame after a negative test. We therefore advocate a distinction between the logical and epistemic formulations of Duhem's problem, the latter relying upon additional relevant information about the system being tested. Recognition of the role of this additional information suggests that some proposed solutions to the epistemic form of Duhem's problem are preferable over others.